ACCURATE AND PRECISE DETERMINATION OF LI ISOTOPIC COMPOSITIONS BY MULTI-COLLECTOR SECTOR ICP-MS - Tomascak P.B.; Carlson R.W.; Shirey S.B. (My University, 1999)
A new method is presented for the preparation of geological materials (water and rock) and their accurate analysis, by multiple collector magnetic sector ICP-MS, for the isotopic composition of lithium. Based on multiple duplicate and replicate measurements over an 8-month period, the precision of this technique is conservatively estimated to be +/-1.1%% (2σ population), which is similar to the precision of other methods in current use. The δ7Li (7Li/6Li relative to the L-SVEC standard) determined for Pacific seawater is +31.8. The δ7Li of the basalt standards JB-2 and SRM-688 are +5.1 and +2.8, respectively. The new technique has additional advantages over other methods in small sample size (~40 ng Li), rapid analysis (~2 samples/h) and relative insensitivity to trace element contamination of analyte solutions.
Keywords: LITHIUM ISOTOPES; MAGNETIC SECTOR; ICP-MS; CATION EXCHANGE; MASS FRACTIONATION